UPAYA MENINGKATKAN MINAT DAN PRESTASI BELAJAR SISWA MELALUI METODE COOPERATIVE SCRIPT MATA PELAJARAN BAHASA INDONESIA KELAS VIII-2 SMP NEGERI 8 KOTA TEBING TINGGI - Rusmiaty Sitepu (JURNAL HANDAYANI PGSD FIP UNIMED, 2015)
the purpose of this research is to improve the learning  interest and academic achievement by the eight grade students of 8 State Junior High School Tebing Tinggi in 2014/2015 academic year through Cooperative Script learning. The subjects were all student of eight grade, State Junior High School Tebing Tinggi in academic year 2014/ 2015 which amounted to 34 students. Colleting data in this research is to use test and observation. Descriptive analysis techniques used include data reduction, data presentation, drawing conclusions. Results showed that used of the cooperative script method can improve the  learning  interest and academic achievement. Key word : Cooperative script, learning interest, descriptive analysis techniques